T cells expressing variable elements of T-cell receptor beta 8 and beta 2 chain regulate murine IgE production. - Renz, H (1992)
After sensitization to ovalbumin (Ova) by inhalation of nebulized antigen, BALB/c mice respond with an early rise in IgE but not in IgG anti-Ova antibody production. Our purpose here was to analyze the repertoire of T cells that may contribute to regulating this IgE response. Initial study of Ova-reactive T-cell hybridomas showed that they selectively express the T-cell receptor variable beta-chain (V beta) elements 2, 8.1/8.2, and 14. The frequency of T cells bearing these V beta elements in local draining lymph nodes of the airways and lungs (peribronchial-draining lymph nodes) after Ova inhalation was examined. Local sensitization increased the proportion of V beta 8.1/8.2 T cells in the peribronchial-draining lymph nodes, whereas expression of V beta 2 or V beta 14 was similar in sensitized and nonsensitized animals. In the presence of increased antigen concentrations, V beta 8 and V beta 2 T cells were equally reactive to Ova when cell proliferation was assayed. Coculture of Ova-selected V beta 8 T cells from peribronchial-draining lymph nodes and spleens of sensitized animals with primed splenic B cells increased IgE but not IgG production. The V beta 8 increase in IgE production was related to an increase in numbers of IgE-secreting B cells. In contrast, coculture of Ova-selected V beta 2 T cells with sensitized B cells had no stimulatory effect on either IgE or IgG production. Further, addition of V beta 2 cells to V beta 8 cells inhibited the V beta 8-induced augmentation of IgE production. These data indicate that T cells expressing different T cell receptors or, perhaps, different V beta elements may play different roles in IgE production in sensitized mice.